Functional Analysis of LDLR (Low-Density Lipoprotein Receptor) Variants in Patient Lymphocytes to Assess the Effect of Evinacumab in Homozygous Familial Hypercholesterolemia Patients With a Spectrum of LDLR Activity. Issue 11 (November 2019) - Banerjee, Poulabi; Chan, Kuo-Chen; Tarabocchia, Michel; Benito-Vicente, Asier; Alves, Ana C.; Uribe, Kepa B.; Bourbon, Mafalda; Skiba, Paul J.; Pordy, Robert; Gipe, Daniel A.; Gaudet, Daniel; Martin, Cesar
Abstract : Objective: Homozygous familial hypercholesterolemia is a rare disease usually caused by LDLR (low-density lipoprotein receptor) mutations. Homozygous familial hypercholesterolemia is characterized by markedly elevated LDL-C (low-density lipoprotein cholesterol) levels and an extremely high risk of premature atherosclerotic cardiovascular disease. A phase 2, proof-of-concept study (NCT02265952) demonstrated that evinacumab, a fully human monoclonal antibody to ANGPTL3 (angiopoietin-like 3 protein), reduced LDL-C levels in 9 patients with genotypically confirmed homozygous familial hypercholesterolemia and was well tolerated. The aim of this study was to analyze the effects of evinacumab on LDLR activity in lymphocytes purified from patients in the proof-of-concept study. Approach and Results: LDLR activity was assessed in patient lymphocytes before and after treatment with evinacumab and versus lymphocytes carrying wild-type LDLR, and also in an LDLR-defective Chinese hamster ovary cell line (CHO- ldl A7) transfected with plasmids encoding the LDLR variants. Overall mean peak reduction in LDL-C with evinacumab was −58±18%, occurring between Week 4 and Week 12. Mutations identified in the 9 patients were shown to be pathogenic, with loss of LDLR activity versus wild type. Two of the LDLR variants, p.(Cys681*) and p.(Ala627Profs*38), were class 2 type mutations that are retained in the endoplasmic reticulum. Six variants were class 3 type mutations with impaired LDL-C binding activity: p.(Trp87Gly), occurring in 2 patients, p.(Gln254Pro), p.(Ser177Leu), p.(Gly335Val), and p.(Ser306Leu). Evinacumab had no effect on LDLR activity. Conclusions: These results suggest that evinacumab is effective for lowering LDL-C in patients with homozygous familial hypercholesterolemia, and the inhibition of ANGPTL3 in humans lowers LDL-C in a mechanism independent of the LDLR. Abstract : Supplemental Digital Content is available in the text.